2014
DOI: 10.1007/s00787-014-0624-x
|View full text |Cite
|
Sign up to set email alerts
|

Suicidality and hospitalization as cause and outcome of pediatric psychiatric emergency room visits

Abstract: The aim of this study was to identify predictors of suicidality in youth presenting to a pediatric psychiatric emergency room service (PPERS). To this end, we conducted a retrospective cohort study of youth aged <18 years consecutively assessed by a PPERS 01.01.2002-12.31.2002, using a 12-page semi-structured institutional evaluation form and the Columbia Classification Algorithm for Suicide Assessment. Multivariate regression analyses were conducted to identify correlates of suicidal thoughts and attempts/pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 36 publications
2
20
1
Order By: Relevance
“…In this sample, 70% of youths were hospitalized after presenting with either suicidal ideation or behavior to an ED, while approximately 30% were sent home. This discharge rate is lower than a recently reported sample of 265 suicidal adolescents, in which 58.5% were discharged home (Grudnikoff et al., ). This higher rate of hospitalization in our sample may be related to the chosen sites for the study.…”
Section: Discussioncontrasting
confidence: 60%
“…In this sample, 70% of youths were hospitalized after presenting with either suicidal ideation or behavior to an ED, while approximately 30% were sent home. This discharge rate is lower than a recently reported sample of 265 suicidal adolescents, in which 58.5% were discharged home (Grudnikoff et al., ). This higher rate of hospitalization in our sample may be related to the chosen sites for the study.…”
Section: Discussioncontrasting
confidence: 60%
“…The fact that an unstable family situation proved to be a predictor of emergency admission adds to the findings of previous studies. Two factors increased the chance that a child would be admitted after emergency consultation: the parents' absence from the consultation and if a child's having been adopted [15,16]. Similarly, the risk of psychiatric hospitalization of children in regular psychiatric outpatient care has been found to be influenced by a family's level of distress, parental capacity to contain the child, and the primary caregivers' marital status [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have identified demographic characteristics and clinical factors as predictors of voluntary admission of young patients seen in psychiatric crisis situations [15][16][17][18]. Demographic characteristics that were found to be associated with decisions to hospitalize children and adolescents after emergency consultation were relatively older age, minority status, and having been adopted [16][17][18][19]. Clinical factors that were associated with a higher chance of admission were suicide attempt or self-injurious behavior, the clinician's appraisal of high suicide risk, the presence of a depressive or bipolar disorder, the severity of psychiatric symptoms, comorbidity, a lower score on the global assessment of functioning (GAF), and prior admission.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations